Tradução e estudo de The Prelude, de William Wordsworth - Aguiar, Angiuli Copetti de (2022)
The poem The Prelude (1850) by the English Romantic poet William Wordsworth (1770 – 1850) presents a multiplicity of dimensions which make it an interesting challenge for the translator. As autobiography, and as part of Wordsworth’s project for a poetry stripped of artificiality, it has a confessional and intimist tone in a diction near to prose, but as an epic in the miltonic tradition, and of Romantic effusion, it is also a poem of lofty rhetoric and sublime scope. Its diction appears to be prosaic, but it remains in a productive tension with the formal structure of its rigorous blank verse. Thus, in order to translate this work the translator must embrace the variety of its registers and comprehend the interaction and tension which take place between them in the production of the total effect of the poem. This we had in mind, and as the objective of our thesis: to study The Prelude, with an special emphasis on its form and language, in order to recreate in Portuguese a text which would reproduce the elements and effects identified as fundamental components of the original text. Thus, we studied the relevant biography of the poet and the history of composition of the poem, as well as its first reception, so as to highlight, among the visions of the poem, our reading of it as a sublime epic. Next, we studied the metrical dimension of the poem, considering Wordsworth’s ideas concerning metrification, the history and the characteristics of the iambic pentameter and the blank verse (meter of Prelude), and Wordsworth’s particular blank verse, establishing the importance of the regular meter in the poem and of its rhythmic regularity. After, we explored the linguistic dimension of the work, analysing, on the one hand, its diction and rhetoric, and, on the other, its vocabulary and syntax to determine the linguistic aspects worthier of attention during the translation, established as: middle style, differentiation of register and diction, epic rhetoric, syntactical complexity, sense of abstration, and sense of passivity. Thus, we delimited our translational perspective as an attempt to recreate in Portuguese the aspects of the poem listed as most relevant through mostly functional correspondences, prioritizing a certain degree of foreignization of the syntax. We performed, then, a survey and brief consideration of the previous translations of the poem and described the course we took during the practice of the translation, until the consolidation of the parameters adopted as ideal for our project, specially the iambic dodecasyllabic verse with particular rules. Finally, we presented our translation and commented the strategies employed in its realization.